All Days 2011
DOI: 10.2118/140542-ms
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Completion Optimization Of Multiple Laterals In Gas Shale Reservoirs: Integration of Geology, Log, Surface Seismic, and Microseismic Information

Abstract: Multidisciplinary data integration combined with the deployment of proper technology is key to optimizing shale gas completions. This paper focuses on the real-time completion optimization of multiple laterals drilled from the same well pad in shale gas reservoirs. These laterals are spaced as close as a few hundred feet laterally with varying vertical landing points. Though these laterals do expose more of the nanodarcy permeability shale rock and increase contact area through fracture stimulation-resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Harpel et al [9] reported that well spacing becomes tighter in parts of the Fayetteville Shale from 600 ft to 400 ft or 300 ft, leading to fluid and proppant volume reductions, while further optimization of stimulation design, especially fracture half-length, is very much required for future development. Ramakrishnan et al [10] suggested that it is particularly challenging to optimize the stimulation treatment in a multi-well design drilled with few hundreds feet of spacing between one another to maximize coverage around each horizontal well, because the optimization process involves perforation and stage placements, sequential stimulation of these wells, fluid and proppant schedules, treatment rates, and application of diversion technology in an effort to achieve effective stimulation along these wells and between the wells. Hence, a detailed study and a comprehensive approach for optimization of fracturing design and multi-well placement are still significantly necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Harpel et al [9] reported that well spacing becomes tighter in parts of the Fayetteville Shale from 600 ft to 400 ft or 300 ft, leading to fluid and proppant volume reductions, while further optimization of stimulation design, especially fracture half-length, is very much required for future development. Ramakrishnan et al [10] suggested that it is particularly challenging to optimize the stimulation treatment in a multi-well design drilled with few hundreds feet of spacing between one another to maximize coverage around each horizontal well, because the optimization process involves perforation and stage placements, sequential stimulation of these wells, fluid and proppant schedules, treatment rates, and application of diversion technology in an effort to achieve effective stimulation along these wells and between the wells. Hence, a detailed study and a comprehensive approach for optimization of fracturing design and multi-well placement are still significantly necessary.…”
Section: Introductionmentioning
confidence: 99%